Histological Description of Hedgehog (Hemiechinus auritus) Abdomen Skin - Al-Zubaidi KA (Journal of Global Pharma Technology, 2019)
The present study was conducted on six healthy male’s hedgehog, to distinguish the normal histology of the abdomen skin. The hedgehogs were anesthetized by ketamine (15 mg/kg. body weight) injected intramuscular after scarfing of hedgehogs, the skinning of the ventral surface of the abdomen was carried out, then the skin specimens fixed in the formalin (10%). Routein histological processes were done. The histological structure of the hedgehog abdomen skin was revealed many invaginations of the skin folds projected from superficial surface; these folds had many bifurcation were divided by grooves, and the folds appeared as the ridges. The abdomen skins of hedgehog covered by keratinized squamous epithelium, the keratin layer consider as protective layer foe the superficial skin which represented the epidermis. Under lining the epithelium there was loose connective tissue that supported the superficial skin; and consisted of collagenous and elastic fibers as well as cellular elements such as fibroblasts, lymphocytes, myoid cells were distributed among collagen and elastic fibers which extended into the cores of the abdomen skin folds. Beneath the loose connective tissue, the dermal spines follicles were found and surrounded via a layer of smooth muscle fibers. Clusters of sweat glands were distributed deeply under the dermal spines follicles. Striated muscle fibers below the sweat glands. The striated muscle fibers were arranged; circular, longitudinal and oblique in the orientation, these muscle fibers which support the upper layer of the skin. The dermal papillae was absent in the hedgehog skin. Keywords: (hedgehog, Histology, Abdomen skin).